Using extended valence framework to examine factors that influence the usage of mobile money in South Africa - Moabi, Rankali (My University, 2020)
Purpose –The purpose of this study is to examine factors that influence usage of mobile money in South Africa applying Extended Valence Framework as the underpinning model. Design/methodology/approach – A survey was conducted using a validated questionnaire. Data was collected from 279 respondents using both probability and non-probability sampling. This study used structural equation model (SEM) (using Smart PLS 2.0M3) to test the proposed model and the hypotheses. Findings – The model explains 50.8% of the variance in the actual use of mobile money. Trust and utilitarian value were found to have significant positive effect on behavioural intention to use mobile money. In addition, personal innovativeness in information technology (PIIT) was found to have a significant positive effect on both trust and perceived risk. However, perceived risk was found to have a significant negative effect on behavioural intention to use mobile money. Furthermore, hedonic value and social influence were found to have no effect in the actual use of mobile money. Research limitations/implications – The study developed and tested a research model underpinned by Extended Valence Framework. The extension of the model using PIIT and utilitarian value further enriches the Extended Valence Framework. In addition, this study contributes to the literature regarding factors influencing usage of mobile money. Lastly, while previous studies used students as proxy for the population of study, the actual users of mobile money were used for data collection in this study. Practical implications – This study helps mobile money practitioners and service providers, especially banks, to better understand the effect of trust, risk, utilitarian value and PIIT on consumers’ perception about usage of mobile money. In addition, practitioners and service providers can use this knowledge to mitigate risk perceptions that consumers may have about mobile money. Originality/value – This study extends Extended Valence Framework using hedonic value, utilitarian value, PIIT and SI
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce in Information Systems to The Faculty of Commerce, Law and Management University of The Witwatersrand, Johannesburg, 2020